Isolation of Arsenic Resistant Escherichia coli from Sewage Water and Its Potential in Arsenic Biotransformation - Basanta Bista; Sangita Shakya (Journal of Tropical Life Science, 2017)
Arsenic contamination in drinking water from ground water poses a threat to the health of a large population in developing countries in Asia. This has sparked great interests in the potential of different microbes in arsenic resistance and removal from water. This study involves isolation of arsenic resistant Escherichia coli from sewage water from Kathmandu University and investigation of its attributes. Arsenic resistant E. coli was successfully isolated which could survive in high concentration of arsenic. The maximum tolerance of arsenite was 909.79 mg/L (sodium arsenite) and 3120.1 mg/L arsenate (sodium arsenate) which is well above most natural concentration of arsenic in ground water. This particular E. coli tolerated multiple heavy metal like silver nitrate, cobalt sulphate, cadmium chloride, nickel chloride, mercury chloride, copper sulphate, and zinc chloride at concentration 20 ÂµM, 1 mM, 0.5mM, 1mM, 0.01 mM, 1 mM, and 1 mM respectively which are concentrations known to be toxic to E. coli. Biotransformation of arsenite to arsenate was also checked for by a qualitative silver nitrate technique. This E. coli was able to transform arsenate to arsenite. It showed some sensitivity to Ciprofloxacin, Gentamicin and Nalidixic Acid. As E. coli and its genome are very widely studied, these particular properties have a lot of potential in microbial remediation or microbial recovery of metals and possible recombination approaches.